Challenges of Sustaining Elimination Status of Leprosy in Nepal - Parajuli, Sudip; Pokhrel, Dinesh B; Baskota, Rabindra; Poudyal, Amod; Paudel, Upama (Journal of Institute of Medicine Nepal, 2019)
Introduction: The number of leprosy patients is increasing in Nepal even after declaration of elimination in 2010. The objective of this study was to review the status of leprosy after declaration of elimination in Nepal and to identify challenges to sustain elimination. Methods: This was retrospective study conducted by reviewing the annual data published by Department of Health Services, Ministry of Health, and Government of Nepal from 2010 through 2018. In addition, one year hospital based data (2017/18) was retrieved from records of Department of Dermatology and Venereology, Tribhuvan University Teaching Hospital, Kathmandu, Nepal. Results: The prevalence of leprosy was found to be 0.77/10,000 population in 2010 and 0.99/10,000 in 2018. The numbers of multibacillary (MB) cases (remained more than 50%) outnumbered paucibacillary (PB) cases throughout eight years. Conclusion: The prevalence of leprosy is gradually increasing in Nepal with more number of multi bacillary cases detected in post-elimination era.